Alternative treatments used by breast cancer survivors (Amazon women) - Humańska, Marzena A.; Nowicki, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2009)
Aim of the study: Breast cancer is the most common type of cancer that affects women. Treatment depends on the stage of the disease. In addition to conventional therapies, women often choose alternative treatments. The aim of the study is to estimate the number of Amazon women undergoing alternative therapies. Material and methods: A pilot investigation was carried out among women – members of the Amazon Women’s Club, district Bydgoszcz. 20 women made up the investigative group. The author’s original questionnaire with sociodemographic questions was used in the study. Results: Mean age of the respondents was 56 years. 85% lived in a big city. 3 women lived in the country. As for education level, almost 3/4 of women graduated from secondary schools (11 women), 4 women had a university degree, 2 had vocational level education and 2 primary level education. 35% of the respondents had tried alternative treatments; most of them started these treatments having finished oncological therapy. The most commonly chosen alternative methods were: phytotherapy, chiropractice, Chinese medicine and massage. 50% of the respondents believe that alternative methods may be used only with doctors’ permission. 35% think that alternative medicine is popular because it has fewer side effects and is natural. Most of the respondents claim that alternative methods did not improve their health. Conclusions: 1. The majority of studied women organized into unions in the Amazons Club did not use unconventional therapy (65%); however, 25% of those studied began to apply unconventional treatment after oncological treatment. 2. Among the Amazon women the most popular alternative methods are: phytotherapy, chiropractice, Chinese medicine and massage. 3. According to the majority of Amazon women the use of unconventional therapy should take place on the condition of the agreement and knowledge of the doctor. 4. The use of unconventional treatment according to the majority of the studied Amazons population did not have an influence on the improvement of their state of health.